Afghanistan declassified : a guide to America's longest war - Williams, Brian Glyn (Philadelphia, 2012)
Nearly 100,000 U.S. soldiers were deployed to Afghanistan at the height of the campaign, fighting the longest war in the nation's history. But what do Americans know about the land where this conflict is taking place? Many have come to have a grasp of the people, history, and geography of Iraq, but Afghanistan remains a mystery. Originally published by the U.S. Army to provide an overview of the country's terrain, ethnic groups, and history for American troops and now updated and expanded for the general public, Afghanistan Declassified fills in these gaps. Historian Brian Glyn Williams, who has traveled to Afghanistan frequently over the past decade, provides essential background to the war, tracing the rise, fall, and reemergence of the Taliban. Special sections deal with topics such as the CIA's Predator drone campaign in the Pakistani tribal zones, the spread of suicide bombing from Iraq to the Afghan theater of operations, and comparisons between the Soviet and U.S. experiences in Afghanistan. To Williams, a historian of Central Asia, Afghanistan is not merely a theater in the war on terror. It is a primeval, exciting, and beautiful land; not only a place of danger and turmoil but also one of hospitable villagers and stunning landscapes, of great cultural diversity and richness. Williams brings the country to life through his own travel experiences-from living with Northern Alliance Uzbek warlords to working on a major NATO base. National heroes are introduced, Afghanistan's varied ethnic groups are explored, key battles-both ancient and current-are retold, and this land that many see as only a frightening setting for prolonged war emerges in three dimensions.